The Influece of Workload and Compensation on Employees' Work Stress at PT. Puja Perkasa - Harries Madiistryanto; Ericho Agil Nugrahan (PT. Publikasiku Academic Solution, 2023)
This research aims to determine and analyze the influence of work load and compensation on work stress at PT. Puja Perkasa. The things raised in this research are: a) how big is the influence of work load on work stress at PT. Puja Perkasa, b) how big is the influence of compensation on work stress at PT. Puja Perkasa, c) how big is the influence of workload and compensation on work stress at PT. Puja Perkasa. To determine the influence of the independent variable on the dependent variable partially, the t test is used and to determine the influence of the independent variable on the dependent variable simultaneously, Anova is used. The sample used in this research was 35 people who were saturated samples. The data collection methods used are literature study, documentation and questionnaires. The results of this research show that with an alpha error degree of 0.05 through the t-test it turns out that the Workload variable significantly influences Employee Work Stress, and Compensation significantly influences Employee Work Stress. Simultaneously, through the ANOVA test, these two variables positively and significantly influence employee work stress.